Restoration of spinal cord injury: From endogenous repairing process to cellular therapy - Wu, Yaqi; Tang, Zhijian; Zhang, Jun; Wang, Yu; Liu, Shengwen (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) disrupts neurological pathways and impact sensory, motor and autonomic nerve function. There is no effective treatment for SCI currently. Numerous endogenous cells, including astrocytes, macrophages/microglia, and oligodendrocyte, are involved in the histological healing process following SCI. By interfering with cells during the SCI repair process, some advancements in the therapy of SCI have been realized. Nevertheless, the endogenous cell types engaged in SCI repair and the current difficulties these cells confront in the therapy of SCI are poorly defined, and the mechanisms underlying them are little understood. In order to better understand SCI and create new therapeutic strategies and enhance the clinical translation of SCI repair, we have comprehensively listed the endogenous cells involved in SCI repair and summarized the six most common mechanisms involved in SCI repair, including limiting the inflammatory response, protecting the spared spinal cord, enhancing myelination, facilitating neovascularization, producing neurotrophic factors, and differentiating into neural/colloidal cell lines.